Legal Force Certificate of The Right of Depedency in Destruction of The Object Guarantee Due to Natural Disasters: A Juridical Study - Ferdiansyah Putra Manggala; Dyah Ochtorina Susanti (Rechtenstudent, 2025)
Shelter is a fundamental human need, essential for safety, stability, and well-being. The right to adequate housing encompasses not only the physical structure but also the legal assurance of ownership and the ability to exercise rights over it. Today, fulfilling the need for housing has become increasingly difficult due to the high cost of land and the complexity of residential construction, which, although sometimes affordable, involves intricate legal and administrative procedures. For individuals or communities who already own land, it is imperative to ensure legal protection and certainty regarding their ownership. A Certificate of Ownership provides formal legal recognition and allows the holder to undertake legal actions related to the land, including using it as collateral. One such legal instrument is the Mortgage Rights Certificate, which holds executorial legal force and serves as strong evidence of a creditor’s legal claim. However, complications emerge when the object of collateral is destroyed by natural disasters. In such cases, the legal position of both the debtor and creditor becomes unclear, as current regulations do not address this issue explicitly. Neither the Basic Agrarian Law (Law No. 5 of 1960) nor the Mortgage Rights Law (Law No. 4 of 1996) provide clear provisions regarding the legal force of mortgage rights under such circumstances. Therefore, this study employs a normative juridical approach, using legal literature, statutory regulations, and scholarly analysis to examine the legal consequences of collateral destruction and to explore protective mechanisms for the affected parties.